Discovery of AZD3199, an inhaled ultralong acting β2 receptor agonist with rapid onset of action - Stocks, Michael; Alcaraz, Lilian; Bailey, Andrew; Bonnert, Roger; Cadogan, Elaine; Christie, Jadeen; Dixon, John; Connolly, Stephen; Cook, Anthony; Fisher, Adrian; Flaherty, Alice; Humphries, Alexander; et al. (American Chemical Society, 2014)
A series of dibasic des-hydroxy β2 receptor agonists has been prepared and evaluated for potential as inhaled ultra-long acting bronchodilators. Determination of activities at the human β-adrenoreceptors demonstrated a series of highly potent and selective β2 receptor agonists that were progressed to further study in a guinea pig histamine-induced bronchoconstriction model. Following further assessment by; onset studies in guinea pig tracheal rings and human bronchial rings contracted with methacholine (guinea pigs) or carbachol (humans), duration of action studies in guinea pigs after intratracheal (i. t.) administration and further selectivity and safety profiling AZD3199 was shown to have an excellent over all profile and was progressed into clinical evaluation as a new ultra-long acting inhaled β2 receptor agonist with rapid onset of action.